Cardiac and Pulmonary Diagnoses and Advance Care Planning in Home Health. Issue 4 (November 2022) - Bigger, Sharon E.; Haddad, Lisa; Glenn, Lee
Chronic cardiovascular and pulmonary diseases are prevalent in the US home health population. Heart failure and chronic obstructive pulmonary disease are both chronic and terminal, but they are not always perceived as serious illnesses with imminent death. Therefore, they provide a context for advance care planning that is distinct from the diagnostic contexts of cancer, end-stage renal disease, or dementia. Advance care planning is defined as a process that supports adults at any age or stage of health in understanding and sharing their goals, values, and preferences about future medical care, including the designation of a surrogate decision-maker. This study tests the hypothesis that US home health agencies with higher percentages of patients with chronic cardiovascular and pulmonary conditions have less robust advance care planning protocols. The Spearman correlation coefficient was r  = 0.22 ( S  = 74684, P  = .025, 1-tailed), which was statistically significant and an unexpected finding. The greater percentage of patients with chronic cardiac and pulmonary diagnoses in an agency, the more robust the advance care planning protocol was. This supports our previous findings and existing literature indicating that agencies may be using exacerbation events marked by acute care use as opportunities to initiate or repeat advance care planning.